Pengaruh Service Quality, Food Quality dan Perceived Sacrifice terhadap Behavorial Intention melalui Customer Experience Sebagai Mediasi pada Majestic Cafe Sekayu - Ellisyah Mindari (Universitas Batanghari Jambi, 2022)
This study aims to analyze the effect of the Service Quality, Food Quality and Perceived Sacrifice on Behavioral Intention through Customer Experience as a mediation at Majestic Cafe Sekayu either directly or indirectly. This study uses a quantitative approach with the aim of explaining the position of the variables studied and the relationship between one variable and another. This study is intended to test the hypotheses that have been formulated previously. The results of this study will explain the causal relationship between the variables through hypothesis testing. In this study, the analytical method used is path analysis with path analysis using the SmartPLS program. The results of this study conclude that service quality has a significant effect on customer experience, service quality has no significant effect on behavioral intention, food quality has a significant effect on customer experience, perceived sacrifice has a significant effect on customer experience. Perceived sacrifice has no significant effect on behavioral intention, customer experience has a significant effect on behavioral intention. Indirectly, customer experience as a mediation has a significant effect on service quality on behavioral intention, customer experience as a mediation has a significant effect on perceived sacrifice on behavioral intention, customer experience as a mediation has a significant effect on food quality on behavioral intention.